Stimulation of fracture mineralization by salt-inducible kinase inhibitors - Momenzadeh, Kaveh; Yeritsyan, Diana; Abbasian, Mohammadreza; Kheir, Nadim; Hanna, Philip; Wang, Jialiang; Dosta, Pere; Papaioannou, Garyfallia; Goldfarb, Sarah; Tang, Cheng-Chia; Amar-Lewis, Eliz; Nicole Prado Larrea, Michaela; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Over 6.8 million fractures occur annually in the US, with 10% experiencing delayed-or non-union. Anabolic therapeutics like PTH analogs stimulate fracture repair, and small molecule salt inducible kinase (SIK) inhibitors mimic PTH action. This study tests whether the SIK inhibitor YKL-05-099 accelerates fracture callus osteogenesis.126 female mice underwent femoral shaft pinning and midshaft fracture, receiving daily injections of PBS, YKL-05-099, or PTH. Callus tissues were analyzed via RT-qPCR, histology, single-cell RNA-seq, and μCT imaging. Biomechanical testing evaluated tissue rigidity. A hydrogel-based delivery system for PTH and siRNAs targeting SIK2/SIK3 was developed and tested.YKL-05-099 and PTH-treated mice showed higher mineralized callus volume fraction and improved structural rigidity. RNA-seq indicated YKL-05-099 increased osteoblast subsets and reduced chondrocyte precursors. Hydrogel-released siRNAs maintained target knockdown, accelerating callus mineralization.YKL-05-099 enhances fracture repair, supporting selective SIK inhibitors' development for clinical use. Hydrogel-based siRNA delivery offers targeted localized treatment at fracture sites.